Parametric Analysis and Optimization on Aerodynamic Performance of Optimized Pedestrian Crash Friendly Sedan Front End Profiles - Nor Azman, Afzatul Najwa; Venkatason, Kausalyah; Sivaguru, Shasthri (International Journal of Integrated Engineering, 2026)
This paper offers a multi-objective optimization framework balancing aerodynamic efficiency with pedestrian safety in Vehicle Front-End (VFE) design. While lowering the Head Injury Criterion (HIC) to lower pedestrian injury risks in crash, the aim is to minimize the drag coefficient (Cd) for enhanced fuel economy and vehicle dynamics. Seven main design parameters such as windshield angle, hood edge height, and bumper centre height were investigated using a Central Composite Design (CCD) technique on Cd and HIC. Using MATLAB's MBC toolbox, response surface models were created; optimization was done using Genetic Algorithms (GA) in MATLAB's Solver-Based Optimize Live Editor Task. A successful predictive modelling was ensured by the fitness function, which maximized the R2 value (89.2% for Cd and 81.7% for HIC) and minimized the root mean square error (RMSE) (0.0065 for Cd and 0.01 for HIC). The optimal model was able to obtain a Cd of 0.1908 and an HIC of 99.7241, respectively, out of the total of 79 different VFE design alternatives that were developed.   Computational fluid dynamics (CFD) validation using ANSYS yielded an 11.74% error within allowable engineering tolerance a simulated Cd of 0.2132. The results show the great relevance of hood edge height and windshield angle in order to increase aerodynamics and pedestrian safety. This work shows the effectiveness of incorporating evolutionary optimization, CFD, and safety analysis, so establishing a logical trade-off strategy for VFE design that enhances both aerodynamic performance and pedestrian protection.